#64 Common Admission Diagnoses for Children Hospitalized with Respiratory Syncytial Virus and Antibiotic Administration Practices in Amman, Jordan. (14th June 2022) - Rankin, Danielle A
Abstract: Background: Determining the etiologic pathogen for acute respiratory infections is challenging, especially in low- and middle-income countries, where diagnostic testing is limited. These barriers may contribute to antibiotic overuse for viral infections. We aimed to evaluate the antibiotic administration patterns among hospitalized children with a research positive test for respiratory syncytial virus (RSV). Method: Children admitted to a government-run hospital in Amman, Jordan with acute respiratory symptoms and/or fever from January 8 to March 17, 2020, were eligible for enrollment. Trained personnel conducted interviews and chart abstractions using a standardized data collection form. Nasal and/or throat swabs were collected and tested for RSV by PCR. Differences between the three most common admission diagnoses for RSV-positive children [bronchiolitis, bronchopneumonia (BP), and pneumonia] were evaluated. Results: A total of 531 children were enrolled and tested and 401 (76%) were RSV-positive, of which 96% received an antibiotic and 25%, 26%, and 32% had an admission diagnosis of bronchiolitis, BP, or pneumonia, respectively. Compared to bronchiolitis and BP, RSV-positive children with a pneumonia were younger and more likely to require supplemental oxygen, receive an antibiotic during hospitalization, be admitted to the ICU; but were less likely to present with wheezing and to report antibiotic use prior to hospitalization (Table 1). RSV-positive children with BP were more likely to present with fever and have a higher C-reactive protein compared to the other diagnoses, whereas bronchiolitis was less likely to be administered antibiotics overall, but more likely to be given a macrolide. Conclusion: Our results suggest that clinical presentation alone is insufficient in correctly determining causative pathogens that warrant empiric antibiotics. Thus, evaluating the role of point-of-care diagnostic testing in resource-limited settings is important and may help limit antibiotic use.